PURWARUPA SISTEM LENGAN ROBOT PEMUTAR BAUT BERDASARKAN WARNA - , IQBAL RIZA FATHUDDIN, Drs. Panggih Basuki, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The sytem gearing baut automatic use colour sensor RGB witd LDR (Light Dependent Resistant) as catcher colour wave to its bounced by led rgb. Light to its bounced led rgb will concern object to its appropriated by program on file and then ldr catching as input with movement arm robot what its continued with gear dc motor as respon. colour object to acceptanced can its arranged user by means of program. Dc motor and servo motor what integrated with microcontroler as movement arm robot gear to move based input colour as well as lcd 16 x 2 for displaying ratio value colour to when process calibration too displaying introduction process move system, all of controled by ATmega 32 as microcontroler what fuse to minimum system. Based of sum triel can its conclusion tools can work with fine , as well as read color to input in sensor. the move motors basse program, strain to components in system tool of stable. How ever for measuring colour limited to distance between 2 cm.